(untitled) (Global Journal of Medical Research, 2014)
Patella fractures and patellar tendon ruptures are mainly due to trauma. Concurrent bilateral patella fracture or concurrent bilateral patellar tendon rupture are even rare. There are case reports that describe concurrent bilateral patella fracture or concurrent bilateral patellar tendon rupture in the literature. This study reports a case of a 23-year-old man who suffered concurrent patella fracture with contralateral patellar tendon rupture due to fall from height by a lift. To our knowledge, this case report describes the first concurrent patellar tendon rupture with contralateral patella fracture.